Mechanisms of Trained Innate Immunity in oxLDL Primed Human Coronary Smooth Muscle Cells - Schnack, Lucia; Sohrabi, Yahya; Lagache, Sina M. M.; Kahles, Florian; Bruemmer, Dennis; Waltenberger, Johannes; Findeisen, Hannes M. (Frontiers in Immunology, 2019)
Objective: Damage and pathogen associated molecular patterns such as oxidized low-density lipoprotein (oxLDL) or bacilli Calmette-Guerin (BCG) vaccine can induce long term pro-inflammatory priming in monocytes and macrophages due to metabolic and epigenetic reprogramming – an emerging new concept called trained innate immunity. Vascular smooth muscle cells express pattern recognition receptors involved in trained innate immunity in monocytes. Here we investigated whether the mechanisms of trained innate immunity also control a proinflammatory phenotype in human coronary smooth muscle cells. Methods: Human coronary smooth muscle cells were primed with oxLDL or BCG for 24h. After a resting time of 4 to 7 days, the cells were restimulated with either PAM3cys4, LPS or TNFα and cytokine production or mRNA expression were measured. Then, mechanisms of monocyte trained innate immunity were analyzed in smooth muscle cells, including receptors, intracellular pathways as well as metabolic and epigenetic reprogramming Results: Priming with oxLDL or BCG lead to a significantly increased production of IL-6, IL-8 and MCP-1 following restimulation. OxLDL priming had little effect on the expression of macrophage or SMC marker genes. Proinflammatory priming of smooth muscle cells induced mTOR-HIF1α-signaling and could be blocked by mTOR-, TLR2- and TLR4-inhibition. Finally, metabolic and epigenetic mechanisms of trained innate immunity in monocytes could be replicated in smooth muscle cells, including increased glucose consumption, lactate production, responsiveness to 6-fluoromevalonate and mevalonate treatment and inhibition of priming by the histone methyltransferase inhibitor methylthioadenosine (MTA). Conclusion: We demonstrate for the first time that mechanisms of the so called trained innate immunity control a proinflammatory phenotype in non-immune cells of the vascular wall. Our findings warrant further research into the specificity of trained innate immunity as an immune cell response as well as the mechanisms of vascular smooth muscle cells inflammation.